A nontoxic dose of chrysotile can malignantly transform Met‐5A cells, in which microRNA‐28 has inhibitory effects. Issue 11 (22nd April 2021) - Zhang, Fangfang; Yuan, Xiuyuan; Sun, Hongjing; Yin, Xianhong; Gao, Yanan; Zhang, Min; Jia, Zhenyu; Yu, Min; Ying, Shibo; Xia, Hailing; Ju, Li; Xiao, Yun; et al.
Abstract: Chrysotile, which is classified as a class I carcinogen by the International Agency for Research on Cancer (IARC), has extensive application in the industry and can lead to lung or other cancers. However, whether chrysotile causes malignant mesothelioma and its molecular mechanism remain debatable. Thus, this study aimed to demonstrate the mesothelioma‐inducing potential of chrysotile at the mesothelial cellular level and the function of microRNA‐28 in malignantly transformed mesothelial MeT‐5A cells. MeT‐5A cells malignantly transformed by a nontoxic dose of chrysotile were named Asb‐T, and miR‐28 expression was downregulated in Asb‐T cells. Restoration of miR‐28 expression inhibited the proliferation, migration and invasion of Asb‐T cells. We verified that IMPDH is a putative target of miR‐28. The expression of IMPDH was significantly higher in Asb‐T MeT‐5A cells than in control cells, whereas the opposite trend was observed with miR‐28 overexpression. Additionally, inhibition of IMPDH had similar effects as miR‐28 overexpression. After miR‐28 was elevated or IMPDH was inhibited, Ras activation was reduced, and its downstream pathways (the Erk and Akt signalling pathways) were inhibited. Surprisingly, the content of miR‐28 in the blood of mesothelioma patients was higher than that in control subjects. Overall, nontoxic doses of chrysotile can cause malignant transformation of MeT‐5A cells. Moreover, miR‐28 inhibits the proliferation, migration and invasion of Asb‐T MeT‐5A cells, negatively regulates the expression of IMPDH through the Ras signalling pathway and may be an important therapeutic target. Abstract : Nontoxic doses of chrysotile caused Met‐5A cells to appear malignant cell characteristics. iR‐28 regulates the proliferation, migration and invasion of malignant transformed Met‐5A cells through IMPDH‐Ras‐GTP‐Raf pathway and may be an important therapeutic target of MPM. The level of miR‐28 in MPM patients was higher than that in normal subjects.